2000
DOI: 10.1063/1.481790
|View full text |Cite
|
Sign up to set email alerts
|

Prereactive evolution of monoalkenes excited in the 6 eV region

Abstract: Articles you may be interested inEffect of chemical substitutions on photo-switching properties of 3-hydroxy-picolinic acid studied by ab initio methods J. Chem. Phys. 140, 084301 (2014); 10.1063/1.4865815 On the origin of ultrafast nonradiative transitions in nitro-polycyclic aromatic hydrocarbons: Excited-state dynamics in 1-nitronaphthalene J. Chem. Phys. 131, 224518 (2009); 10.1063/1.3272536Mass-analyzed threshold ionization study of vinyl bromide cation in the first excited electronic state using vacuum-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
92
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 48 publications
(65 reference statements)
13
92
1
Order By: Relevance
“…Since the equilibrium geometry of the cation is only weakly twisted, 50 it is plausible that strongly twisted ethene molecules cannot be ionized with the probe pulses employed in the experiments. 48,49 The measured lifetimes are indeed in good agreement with the calculated time scale of twisting of ethene in the V state ͑cf. Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Since the equilibrium geometry of the cation is only weakly twisted, 50 it is plausible that strongly twisted ethene molecules cannot be ionized with the probe pulses employed in the experiments. 48,49 The measured lifetimes are indeed in good agreement with the calculated time scale of twisting of ethene in the V state ͑cf. Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Systematic chemical substitutions were used to discern the roles of electronic structure, density of states, and floppiness or rigidity in electronically nonadiabatic dynamics in substituted benzenes 8 and ethylenes. 9 Further studies on a substituted ethylene directly revealed vibrational wavepacket motions induced by passage through a conical intersection. 10 In a recent, detailed study on excited state dynamics in the R, -enones, 11 the location of a methyl substituent on acrolein (2-propenal) was shown to lead to very different photodynamics, despite the relative energetics and topologies of the CI's being very similar for all molecules concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Time dependent spectroscopy can probe very fast relaxation processes immediately after excitation with a resolution determined only by the autocorrelation time of the pump and probe pulses. Electronic relaxation, resulting from non adiabatic couplings between the electronic states involved, is effected via a wavepacket motion after the ultrafast excitation (Mestdagh et al, 2000). The wavepacket goes through the funnels of the conical intersections into the surfaces of lower electronic states.…”
Section: Photophysics Of Porphyrin Systemsmentioning
confidence: 99%